Bidirectional inward migration of particles lagging behind a Poiseuille flow in a rectangular microchannel for 3D particle focusing. (22nd January 2015) - Kim, Young Won; Yoo, Jung Yul
Abstract: Electrophoretic mobility of particles dispersed in an electrolyte solution induces the particles to lag behind a Poiseuille flow in a rectangular microchannel, which causes bidirectional inward migration of particles to the central axis of the channel. As a result, in the present theoretical and experimental study, three-dimensional (3D) particle focusing is clearly realized in such a manner that the particles are aligned in a single file along the axis of the channel as they are transported downstream. Theoretical prediction on the particle migration time provides an excellent assessment of the experimental results. The method proposed in the present study has potential for development of low-cost rapid manufacturing process of sheathless monolayer microchips for 3D particle focusing.